This FLUX AND WORKPIECE CURRENT DENSITY DISTRIBUTION IN LONGITUDINAL FLUX INDUCTION HEATERS - Nasir, Bilal (IJRDO - Journal of Electrical And Electronics Engineering, 2019)
This work investigates the distribution of flux density and current density on two types of rectangular workpiece, steel (magnetic) und aluminum (nonmagnetic). The workpiece were subjected to travelling fields, which come a longitudinal flux induction heater. For the flux density measurements, search coils of 14 mm diameter were used small pins have been distributed on the surface the two workpiece to measure the current density Constantan wire was used with S.W.G-44.